Effects of Temperature and Additives on NOx Emission From Combustion of Fast-Growing Grass - Liu, Haili; Hong, Qingchao; Liu, Heyun; Huang, Zhen; Zhang, Xu; Chen, Wang; Zeng, Xi; Pan, Shulin (Frontiers in Energy Research, 2021)
Fast-growing grass, as a popular renewable energy, is low in sulfur content, so NOx is the major pollutant during its combustion. To study the emission characteristics of NOx and obtain the data of controlling NOx emission, the effects of combustion temperature as well as the additive type and mass fraction were investigated on the emission characteristics of NOx from the combustion of fast-growing grass. Results revealed that the first peak for NOx emission from this combustion gradually increases with an increase in temperature. Moreover, the additives were found to dramatically impact the amount of NOx emission and its representative peak. The optimal additives and their optimal mass fractions were determined at various specific temperatures to reduce NOx emission. At combustion temperatures of 600, 700, 750, 800, and 850 ℃, the optimal conditions to limit NOx emissions were 5% SiO2, 3% Al2O3, 3% Ca(OH)2, 15% Al2O3, and 3% SiO2 (or 3% Al2O3), respectively; the corresponding emission peaks decreased by 43.59, 44.21, 47.99, 24.18, and 30.60% (or 31.51%), with denitration rates of 63.28, 50.34, 57.44, 27.05, and 27.34% (or 27.28%), respectively.